Trade-offs between food security and forest exploitation by mestizo households in Ucayali, Peruvian Amazon - Andrieu, Nadine; Blundo Canto, Genowefa M.; Cruz García, Gisella S. (Elsevier, 2019)
The Peruvian Amazon is undergoing rapid and uneven economic growth, alongside alarming rates of deforestation, increasing land use change and food security concerns. Although it has been widely acknowledged that food insecurity is intrinsically linked with deforestation, the links have not been thoroughly documented. The aim of this paper is to analyse the trade-offs and synergies between food security and forest exploitation at household level in mestizo communities in Ucayali, one of the regions with the highest deforestation rates in the Peruvian Amazon. To this end, 24 farmers were interviewed, surveys were conducted with a sample of 58 households, and an ad-hoc simulation modelling tool was developed and applied. Four main types of mestizo farming households were identified based on their crop and livestock diversity. For all farm types, the forest mainly represented a set aside area to support a potential increase in agricultural production. However, simulations showed that the different types of households, with different decision rules, lead to different rates of deforestation. The results of this study showed that the most diversified farming households presented the smallest trade-offs between food security and forest conservation, as they are the ones most likely to preserve the forest while ensuring their food security.